Matharpacady-23.jpeg - Mumbai Archive Project Team (Jio Institute, 2024)
Lopez House, at 23D Matharpacady, was the residence of Lt Cdr Eric Lopes and his daughter Dagmar Lopez. On Sundays, Dagmar played Western music on the musical saw (a popular vaudeville instrument, which looks like a flexible carpenter’s handsaw, played with a bow drawn across the non-toothed side by holding the handle between the knees and bending the blade while bowing along the flat edge) accompanied by his brother Ian Lopes on the guitar.